Muumimaailman taikaa - Anttila, Markku; Anttila, Reijo; Hirvijärvi, Minna; Järvelä, Mauno; Kakko, Merja; Kattelus, Mauri; Kivimäki, Petri; Parviainen, Heikki; Ristilä, Timo; Saari, Ari (M. Anttila Production, 1996)
18 kappaletta.